If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(-3x + 2) = 5 Reorder the terms: 5x + 2(2 + -3x) = 5 5x + (2 * 2 + -3x * 2) = 5 5x + (4 + -6x) = 5 Reorder the terms: 4 + 5x + -6x = 5 Combine like terms: 5x + -6x = -1x 4 + -1x = 5 Solving 4 + -1x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 5 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 5 + -4 -1x = 5 + -4 Combine like terms: 5 + -4 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| H=-16t^2+30T-6 | | 2x-5=2x+11 | | 13-5(3x+2y)= | | 1(c+9)=9 | | 35/315 | | 15x-(9x-6)=18 | | (2y+1)+(3x-6y)=2+x | | 12d^2-11dt-15t^2=0 | | -9=2(x-4) | | -9(1/2x-3)= | | 6(x^2)-x-1=0 | | (2y+1)+(3x-6)=2+x | | 6-6x=5x-9x-2x | | 8x/7-3/4=6/2-4x/4 | | 3x+-3=180 | | (2x+4)(x+4)=196+3x | | 10m+6=6m+30 | | x-15=x/77 | | -4p-12=12 | | w+2.9=6.4 | | z^2=-2z-14 | | -3/8t=1/6 | | y=20-3(1) | | g=y-cx | | 8(3n+3)=8(6n+3)+2 | | 3(1.5x+9)= | | 2(3x-2)=3(4x+5)+7X | | 144x=3268.80 | | 5x-12+x=-13 | | 4/3x3.14x3.04^3 | | -4p+8(p+3)=4(p-8)+2 | | 6(x+4)-3x=11 |